Penggunaan Bubuk Kulit Kerang Darah Dan Lokan Sebagai Bahan Pengganti Semen - Revina Oktaviani; Monita Olivia; Ismeddiyanto Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
In this study, two types of waste seashells, including blood clam and lokan used as cement replacement material. The parameters studied include compressive strength, workability, and unit weight. These properties were compared with those of a control concrete that was made of Ordinary Portland Cement (OPC). Based on the mixes using the ground seashell with proportion 2, 4, 6, and 8% by weight of cement, the optimum compressive strength was achieved for the mix that replaced cement by 4%. Incorporation of lokan seashell resulted higher unit weight than other concrete. The result indicate that waste seashells can be applied as cement replacement and may improve the workability of concrete.Keywords: seashells, cement replacement, compressive strength, unit weight, workability